INFLUENCE OF AMOUNT OF RESIDENT AND SPENDING OF GOVERNMENT THROUGH ECOMOMIC’S GROWTH IN NORTH SUMATERA - Alisyah Pitri; Nilfatri Nilfatri; Muhammad Maulana; Irpan Nursukmi (STIA Indragiri, 2020)
Level of through ecomomic’s growth in north sumatera from year to year go through fluktuation, while amount of resident increasingly rise. However spending of government go through raising. Phenomena that was happened not avalaible with theory where , if level of ecomomic’s growth was slow and not go above growth of resident then average klincome pendapatan rata- rata of residen go down. If level of ecomomic’s growth was same with growth of resident, then economic not go through development and raising of prosperty not go through progress. Purpose of this research to know about amount of resident and spending of government influence ecomomic’s growth ekonomi simultaneously. This reserch was done in north sumatera, with kind of reserch quantitative research. Sample wa used amount 30 start from 1987-2016 with design purposive sampling, data was got through SPSS Versi 23. Result of estimation research by using t tes was amount resident influence throgh ekonomic growth with was proved from valueai sig 0,001 < 0,05. And Serta spending of goverment that not influence through economic growth with value sig 0,215 > 0,05. Simultaneously amout of resident and spending of goverment influence through economic growth, with was proved from result Fhitung (113.692) > Ftabel (3,35) or sig 0,000 < 0,05. Big relation between amount of resident and spending of goverment simultaneously throgh economic growth with value R amount 0,945 that show there is strong correlation . with value R square amount sebesar 89 % while 11 % was influnced by another variabl. Key words: amount resident, spending of goverment, and ecomomic’s growth